Thyroid nodule management: clinical, ultrasound and cytopathological parameters for predicting malignancy (Clinics, 2012)
Although fine-needle aspiration cytology is considered to be the reference method for evaluating thyroid nodules, the results are inaccurate in approximately 10-30% of cases. Several studies have attempted to predict the risk of malignancy in thyroid nodules based on age, nodularity, thyrotropin values, thyroid autoimmune disease, hot/cold nodule status, and ultrasound parameters. However, no consensus has been found, and none of these parameters has significantly affected patient management. The management of indeterminate thyroid nodules and re-biopsies of nodules with initially benign cytological results remain important and controversial topics of discussion. The Bethesda cytological system and several studies on the use of molecular markers to predict malignancy from cytological samples of thyroid nodules need further clarification. More in-depth discussions among and continuous education of the specialists involved in treating thyroid disease are necessary to improve the management of these patients. This review aims to examine the clinical, laboratory, ultrasound, and scintigraphic parameters that can be used for thyroid nodule management.